2010
DOI: 10.1002/lary.20850
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of velopharyngeal function after relocation pharyngoplasty for obstructive sleep apnea

Abstract: RP for OSA does not cause velopharyngeal insufficiency in terms of voice, nasality, and articulation in spite of anterior advancement of the soft palate, but does induce a nondetrimental change in nasalance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…UPPP and other previous palatal surgery techniques (e.g., LAUP, UPF) for OSA were based on ablative techniques to remove the uvula and a significant amount of soft palate tissue. Over the years, these procedures were associated with a high incidence of unfavorable postoperative complications and morbidities [13][14][15][16]. In the short and long term, the most typical problems reported in these patients were dysphagia, rhinolalia, velopharyngeal insufficiency and nasopharyngeal regurgitation, phlegm in throat, and abnormal scarring with velopharyngeal stenosis [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UPPP and other previous palatal surgery techniques (e.g., LAUP, UPF) for OSA were based on ablative techniques to remove the uvula and a significant amount of soft palate tissue. Over the years, these procedures were associated with a high incidence of unfavorable postoperative complications and morbidities [13][14][15][16]. In the short and long term, the most typical problems reported in these patients were dysphagia, rhinolalia, velopharyngeal insufficiency and nasopharyngeal regurgitation, phlegm in throat, and abnormal scarring with velopharyngeal stenosis [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In the short and long term, the most typical problems reported in these patients are dysphagia, rhinolalia, velopharyngeal insufficiency and nasopharyngeal regurgitation, phlegm in throat, foreign body sensation, and velopharyngeal stenosis. Another important aspect to keep in mind is postoperative pain, especially during swallowing [12][13][14]. These complications were often reported for UPPP and laser-assisted uvulopalatoplasty (LAUP) where major palate resections were performed [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…While most studies have only focused on noise and light modulation, it is crucial to implement effective protocols to modify other environmental factors as well. In a study in Taiwan, Lee et al, reported that enhancing environmental factors such as light and noise by nurses can affect the sleep quality of ICU patients and reduce their sleep disruption (18). In the United States, Martinez et al, found that reducing noise and light, not even as a protocol but generally, could have a positive impact on the sleep quality of ICU patients (19).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, palatal surgery is commonly performed as the soft palate is considered to be the major snore sound generator . Relocation pharyngoplasty, a modified uvulopalatopharyngoplasty that advances the soft palate and splints the lateral pharyngeal wall, has been proven to be an safe and effective in the treatment of obstructive sleep apnoea (OSA) . However, the effect of relocation pharyngoplasty on snoring is not fully understood.…”
mentioning
confidence: 99%
“…11,12 Relocation pharyngoplasty, a modified uvulopalatopharyngoplasty that advances the soft palate and splints the lateral pharyngeal wall, has been proven to be an safe and effective in the treatment of obstructive sleep apnoea (OSA). [13][14][15] However, the effect of relocation pharyngoplasty on snoring is not fully understood. This study aimed to demonstrate the objective changes of snoring sound after relocation pharyngoplasty using the Snore Map and correlate these with changes in the apnoea-hypopnoea index (AHI) and subjective snoring questionnaire scores.…”
mentioning
confidence: 99%